PREVENTION OF AGGRESIVE BEHAVIOUR IN PUPILS BY DEVELOPING EMOTIONAL INTELLIGENCE ABILITIES - Luminiţa MITROFAN (National Centre for Policy and Evaluation in Education, 2018)
We live in a society where aggressiveness and violence already tend to become a major social problem. Aggressiveness is present in all environments, conditioned by many cultural, environmental and social factors that sometimes influence how it will be expressed and often involve high social costs. In recent years, there has been a sharp rise in aggression and violence in the school environment, which raises concern and the necessity to find effective solutions to combat them. In fact, the problem of school violence was debated at the Utrecht European Commission Conference in 1997, ensuring a safe school environment becoming a major objective for most of the participating countries. The purpose of this article is to highlight the relationship between aggressiveness and emotional intelligence in students, as well as the very important role that emotional skills development programmes have in preventing and combating this phenomenon. Aggressiveness and violence in the school environment requires a frontal approach through the use of effective classroom educational strategies that actively involve students and teachers. Such strategies could be represented by the implementation of socio-emotional development programmes to help students develop emotional skills such as: effective identification and management of negative emotions and stress, empathy, compassion and altruism, cooperation with colleagues and work in team, assertive communication and, last but not least, conflict management skills. When pupils are armed with such skills, they increase school performance, empathy and the quality of social interactions, while reducing the frequency of school discipline issues as well as aggressive manifestations.